Exploring contextual factors affecting first entering students' motivation to learn English at the University of Limpopo - Moleke, Heritage (My University, 2021)
This study aimed to explore contextual factors affecting first entering students' motivation to learn English at the University of Limpopo (UL). It has utilised a qualitative approach and also adopted an exploratory design to explore the contextual factors, which affect students' motivation to learn the English language. Questionnaires and interviews were used to collect data from a selected sample of respondents. Moreover, Thematic Content Analysis (TCA) was employed to analyse and thematise the collected data in line with the objectives of the study, which are aligned with the literature review in the study. The following themes were generated: students' motivations to learn the English language, the students' approaches to learning the English language, the role of context in relation to students' motivation to learn English, the lecture hall control and climate, the effect of lecture hall control and climate on students' motivation, and the lecturers' perceptions about motivation to learn. In addition, the study found that first entering students' motivation to learn the English language was influenced by contextual factors such as lecture hall setting, lecturers' teaching approaches as well as the perceptions of friends and classmates. Therefore, the study recommended that the UL Department of Languages, the lecturers, as well as the Academic Development Centre (ADC) should come up with possible strategies to suggest contextual factors that could motivate the UL first entering students to learn English. Key concepts: Motivation, contextual factors, English L2, first entering students, Self Determination Theory
Thesis (M. A. (English Studies)) -- University of Limpopo, 2021
Keywords: Motivation; Contextual factors; English L2; First entering students; Self determination theory; Achievement motivation in youth; English language -- Study and teaching; College freshmen -- South Africa -- Limpopo